The Utilization of Insects as Feedstuff in Broiler Diet - cecep hidayat (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Insect meal is an unconventional feedstuff and is expected to be an alternative protein source in broiler diet in the future, as an impact of high price and a limited supply of a fish meal. The objective of this paper is to describe the potency of insects as a feedstuff in broiler diet. Some types of insects, i.e., bees, flies, crickets, grasshoppers, termites, ants, and cockroaches have the potential to be a feedstuff protein source. Several studies reported that insect has high protein content (10.3-76.2%). The use of insects as feedstuffs in broiler diet is constrained by several limiting factors, i.e. the presence of chitin, high crude fat content, and the presence of contaminants. Processing insects before being used as feedstuffs is necessary. Separation of chitin and crude fat content are highly recommended before using insect as protein source feedstuff in broiler diet. The use of insects in a broiler diet ranges from 4 to 29.65% depending on the type of insect, life phase of insect and the type of processing. Research and development to increase insect utilization in broiler diet are still needed.